Impact of arm technique and elastic force on vertical jump performance in physical education students: a convergent validation study - Era Deva; Milaim Berisha (Physical Education of Students, 2024)
Background and Study Aim. Vertical jump performance is crucial for athletes in many sports. However, the optimal techniques for maximizing jump height and efficiency for both students and professional soccer players require more effective solutions. This study aimed to investigate the influence of various vertical jump techniques, focusing on arm swing and elastic force utilization, and to evaluate the extent of the impact that each modification has on biomechanical characteristics and performance outcomes.